Reorientation of Rural Development as a Base for Improving Land Ownership Distribution at Farmer Level - Jamal, Erizal (Pengembangan Inovasi Pertanian, 2013)
The problem of unbalanced land distribution at farm level in Â Â  Â Indonesia has hampered many efforts to improve rural livelihoods.Â Â  Â Several development programs that have been implemented by Â Â  Â the government have not been fully benefitted by smallholders Â Â  Â due to various reasons, and in many cases this condition even Â Â  Â further widen inequality, because onlyÂ  landowners who are able Â Â  Â to take advantage the vast range of opportunities created through Â Â  Â the programs. In the future, a reorientation of rural development Â Â  Â is needed with more emphasis on improving farmersâ access to Â Â  Â information, capital, technology, and their capacity to take Â Â  Â advantage of opportunities that are locally available. Reorientation Â Â  Â of rural development will be initiated with changes of the Â Â  Â approaches in the planning and implementation of development, Â Â  Â with emphasis on the development of diverse types of businesses, Â Â  Â as well as capacity building of the community to take advantage Â Â  Â of the growing local opportunities. These efforts need to be Â Â  Â supported by the implementation of rural development with an Â Â  Â integrated approach, through a strong cooperation at the district Â Â  Â level under the coordination of District Development Planning Â Â  Â Agency. Rural development planning should be directed to two Â Â  Â main issues. Firstly, open up new business opportunities, especially Â Â  Â those non-based land activities. Secondly, build the community Â Â  Â capacity to capture the existing business opportunities. The Â Â  Â technologies being developed should be neutral with respect to Â Â  Â farmers land ownership, and the technology dissemination is Â Â  Â supposed to be proportional in order to reach all levels of farmers.Â Â  Â